2020
DOI: 10.1002/ep.13506
|View full text |Cite
|
Sign up to set email alerts
|

Steam reforming of tar from raw coke oven gas over bifunctional catalysts: Effects of preparation parameters on CO2 adsorption performance

Abstract: From the thermodynamic analysis of the steam reforming process of raw coke oven gas, the H2 amplification factor after the reforming can reach the highest (over 3.5) in the temperature range between 650 and 800°C, where the bifunctional catalysts to be prepared should have the best CO2 adsorption performances as well as the excellent reforming catalytic performances. In this article, the bifunctional NiO/CaO@C12A7 catalysts were prepared at different preparation parameters, and among them, the catalyst sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was observed that a comparison of experimental and estimated blend fluidities revealed a propensity for positive synergy between components in terms of fluidity, with the addition of charcoal and coal tar. Zhang et al 55 synthesized the bifunctional NiO/CaO at C12A7 catalysts with reforming catalytic and CO 2 adsorption effects were using various preparation settings, because of the gauge of CO 2 adsorption performances. It was concluded that the H 2 amount after the reforming may be increased to more than 3.5 times the original that in the RCOG at the S/C ratio more than 3.0 in the temperature range between 650 and 800°C, where the developed bifunctional catalysts should have the best CO 2 adsorption characteristics.…”
Section: Recent Studies On Elt Managementmentioning
confidence: 99%
“…It was observed that a comparison of experimental and estimated blend fluidities revealed a propensity for positive synergy between components in terms of fluidity, with the addition of charcoal and coal tar. Zhang et al 55 synthesized the bifunctional NiO/CaO at C12A7 catalysts with reforming catalytic and CO 2 adsorption effects were using various preparation settings, because of the gauge of CO 2 adsorption performances. It was concluded that the H 2 amount after the reforming may be increased to more than 3.5 times the original that in the RCOG at the S/C ratio more than 3.0 in the temperature range between 650 and 800°C, where the developed bifunctional catalysts should have the best CO 2 adsorption characteristics.…”
Section: Recent Studies On Elt Managementmentioning
confidence: 99%
“…As mentioned above, as a carrier, Ca 12 Al 14 O 33 has a special free oxygen storage structure, which can also effectively inhibit the sintering of CaO when carried within Ca 12 Al 14 O 33 (Li et al, 2009). Thus, the double-effect Ni/ CaO-Ca 12 Al 14 O 33 catalyst was prepared and applied to the steam reforming process of 1-methylnaphthalene (C 11 H 10 ) as a tar model component in our previous study, showing a good catalytic activity and CO 2 adsorption capacity (Zhang et al, 2021a;Zhang et al, 2021b). However, the doubleeffect catalyst has not been applied in the reforming of real tar, and because of its component's complexity, the catalytic performance on the reforming process of real reforming may be decreased compared to that on the model component.…”
Section: Introductionmentioning
confidence: 99%